Effect of Roundtable Learning Model on Mathematics Achievement Viewed from The Student Cognitive Style - Astunnisyah Astunnisyah; Budiyono Budiyono; Fajar Surya Hutama (Pancaran Pendidikan, 2017)
This study was conducted to determine effect of roundtable learning model and cognitive style on mathematics achievement. This research was quasi experimental research with factorial design 1 x 2. The sample of research consist of 88 students. The data in the research was two ways analysis of variance with unequal cells, with the 5% level of significance. The results of the research were as follow:. (1) Students who have field independent cognitive style have better mathematics achievement than student who have the field dependent cognitive style:. (2) In roundtable model, students who have field independent cognitive style have better mathematics achievement than students who have the field dependent cognitive style.